Development of Merdeka Curriculum Teaching Modules focused on Green Chemistry Materials - Setyowati, Giyarsih; Siregar, Lamtiar Ferawaty; Pongkendek, Jesi Jecsen; Parlindungan, John Yoro (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To find out the procedure for developing Merdeka Curriculum teaching modules on green chemistry material and producing products in the form of teaching modules on green chemistry material that are valid and practical. Methodology: This type of research is R&D using the 4D model, but in this study, it only reached the 3D stage, namely Define, Design, and Develop. The subjects of this study were 2 people validating the teaching module, 5 teachers responding, and 34 students of class X/Phase E of Senior High Scool 2 Merauke. The instruments used in data collection were interviews, questionnaires, and validation. Main Findings: The results of this study indicate that the Merdeka curriculum teaching module on green chemistry material from the product validation assessment is 95% with a very valid category. Reviewed from the practicality aspect, it can be seen from the teacher response assessment of 92% with a very practical category. Based on the results of the study, the Merdeka curriculum teaching module on green chemistry material is declared valid and practical to use. Novelty/Originality of this study: The teaching modules that are compiled are integrated with student abilities, facilities and infrastructure of Phase E at Senior High Scool 2 Merauke, assessments, materials are integrated with the local context. The teaching modules that are compiled are adjusted to the students' learning styles and have been validated by the validator.